Uncovering the signalling, structure and function of the 20‐HETE‐GPR75 pairing: Identifying the chemokine CCL5 as a negative regulator of GPR75. (15th June 2021) - Pascale, Jonathan V.; Park, Eon Joo; Adebesin, Adeniyi Michael; Falck, John R.; Schwartzman, Michal Laniado; Garcia, Victor
Abstract : Background and Purpose: The G‐protein‐coupled receptor GPR75 (Gq) and its ligand, the cytochrome P450‐derived vasoactive eicosanoid 20‐hydroxyeicosatetraenoic acid (20‐HETE), are involved in the activation of pro‐inflammatory and hypertensive signalling cascades contributing to diabetes, obesity, vascular dysfunction/remodelling, hypertension and cardiovascular disease. Little is known as to how, where and with what affinity 20‐HETE interacts with GPR75. Experimental Approach: To better understand the pairing of 20‐HETE and its receptor (GPR75), we used surface plasmon resonance (SPR) to determine binding affinity/kinetics. The PRESTO‐Tango receptor‐ome methodology for GPR75 overexpression was coupled with FLIPR Calcium 6 assays, homogeneous time‐resolved fluorescence (HTRF) IP‐1 and β‐arrestin recruitment assays to determine receptor activation and downstream signalling events. Key Results: SPR confirmed 20‐HETE binding to GPR75 with an estimated K D of 1.56 × 10 −10 M. In GPR75 ‐transfected HTLA cells, 20‐HETE stimulated intracellular Ca 2+ levels, IP‐1 accumulation and β‐arrestin recruitment, all of which were negated by known 20‐HETE functional antagonists. Computational modelling of the putative ligand‐binding pocket and mutation of Thr212 within the putative 20‐HETE binding site abolished 20‐HETE's ability to stimulate GPR75 activation. Knockdown of GPR75 in human endothelial cells nullified 20‐HETE‐stimulated intracellular Ca 2+ . The chemokine CCL5, a suggested GPR75 ligand, binds to GPR75 ( K D of 5.85 × 10 −10 M) yet fails to activate GPR75; however, it inhibited 20‐HETE's ability to activate GPR75 signalling. Conclusions and Implications: We have identified 20‐HETE as a high‐affinity ligand for GPR75 and CCL5 as a low‐affinity negative regulator of GPR75, providing additional evidence for the deorphanization of GPR75 as a 20‐HETE receptor. Abstract :